2019
DOI: 10.22617/wps190617-2
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Natural Disasters on Households and Small Businesses in India

Abstract: The views expressed in this publication are those of the authors and do not necessarily reflect the views and policies of the Asian Development Bank (ADB) or its Board of Governors or the governments they represent. ADB does not guarantee the accuracy of the data included in this publication and accepts no responsibility for any consequence of their use. The mention of specific companies or products of manufacturers does not imply that they are endorsed or recommended by ADB in preference to others of a simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Their results indicate that none of these measures are sufficient to meet the losses caused by the flood. Patankar (2019) found that the compensation paid by the public agencies to affected households to cover their losses due to floods in three cities (Mumbai, Chennai and Puri) was inadequate. Households who are below the poverty line generally resort to borrowings as a coping mechanism, which pushes them into a debt trap and further impoverishment.…”
Section: History Of Disasters In Chennai and Its Impact On Informal S...mentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicate that none of these measures are sufficient to meet the losses caused by the flood. Patankar (2019) found that the compensation paid by the public agencies to affected households to cover their losses due to floods in three cities (Mumbai, Chennai and Puri) was inadequate. Households who are below the poverty line generally resort to borrowings as a coping mechanism, which pushes them into a debt trap and further impoverishment.…”
Section: History Of Disasters In Chennai and Its Impact On Informal S...mentioning
confidence: 99%
“…During the 2015 floods, Patankar (2019) recorded five types of damage (i) house structure, (ii) household assets, (iii) appliances, (iv) vehicles and (v) work tools. In their study on the extent of damage and recovery process after the floods in 2015, Joerin et al (2018) find that while physical assets (housing and infrastructure) took too long to be recovered in most affected areas, socio-economic losses (such as income, employment, physical and mental health, nutrition, education and culture) took even longer to be restored.…”
Section: History Of Disasters In Chennai and Its Impact On Informal S...mentioning
confidence: 99%
“…Based on the Global Climate Risk Index 2021, developed by the organization Germanwatch, India ranks 7 out of 10 in terms of the most affected countries in 2019 (Eckstein et al , 2021). India, one of the most disaster-prone countries in the world, records the highest mortality and damages due to hydrological disasters ever since the 1990s (Patankar, 2019). As per the Central Water Commission of India, during the period 1952–2018, floods in India resulted in the loss of over a hundred thousand lives and economic damage worth INR 4.69tn (Mahapatra, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A large proportion of people in India are affected by floods and landslides during the monsoon season (Nanditha and Mishra, 2021; George et al , 2021). The vulnerable sections of society will be affected disproportionately by the direct and indirect impacts of flooding (Adelekan, 2010; Chatterjee, 2010; Jongman, 2018; Patankar, 2019; Winsemius et al , 2016). Analysis of vulnerability is needed to achieve successful disaster risk reduction (Proag, 2014).…”
Section: Introductionmentioning
confidence: 99%